Preparation and characterization of sodium thiosulfate pentahydrate/silica microencapsulated phase change material for thermal energy storage - Liu, Chenzhen; Wang, Cui; Li, Yimin; Rao, Zhonghao (RSC advances, 2017)
Microencapsulated phase change materials (MicroPCM) were successfully fabricated by encapsulation of sodium thiosulfate pentahydrate (SoTP) as core with silica shell using sol-gel method. The chemical structure, phase analysis, surface morphology, thermal properties and thermal stability of the MicroPCM were tested using X-ray diffraction instrument (XRD), X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and thermogravimetric analyzer (TG), respectively. The effects of core/shell mass ratio, concentration of emulsifier and stirring rate on the morphology of MicroPCM were studied. In addition, the core/shell mass ratio impact on the latent heat, thermal stability and supercooling of MicroPCM were also tested. The results indicates that the MicroPCM have relatively spherical shape. The encapsulation ratio of MicroPCM decrease with the decrease of SoTP mass percentage. The thermal properties and supercooling degree have been greatly improved. The highest encapsulation ratio of the MicroPCM is 94.65%. The thermal conductivity of SoTP is improved from 0.6035 to 0.7718 W (m k) −1 after the encapsulation of SoTP with silica. Depending on all results, it can be concludes that the prepared SoTP/silica MicroPCM have great potential for being used in thermal energy storage applications. Microencapsulated phase change materials (MicroPCM) were successfully fabricated by encapsulation of sodium thiosulfate pentahydrate (SoTP) as core with silica shell using sol-gel method.